2022
DOI: 10.1021/acschemneuro.2c00765
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Map of the Influence of Biomimetic Lipid Model Membranes on Aβ42 Aggregation

Abstract: The aggregation of the amyloid β (Aβ) peptide is one of the molecular hallmarks of Alzheimer’s disease (AD). Although Aβ deposits have mostly been observed extracellularly, various studies have also reported the presence of intracellular Aβ assemblies. Because these intracellular Aβ aggregates might play a role in the onset and progression of AD, it is important to investigate their possible origins at different locations of the cell along the secretory pathway of the amyloid precursor protein, from which Aβ i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Several different techniques have been successfully applied for the characterisation of molecular interactions in research, such as dynamic light scattering (DLS) (Malm and Corbett, 2019), isothermal titration calorimetry (ITC) (Pierce et al, 1999), microscale thermophoresis (MST) (Asmari et al, 2018), nuclear magnetic resonance (NMR) (Wilkins et al, 1999), surface plasmon resonance (SPR) (Mullett et al, 2000;Visentin et al, 2016Visentin et al, , 2018, and the here presented microfluidic diffusional sizing (MDS) (Arosio et al, 2016;Scheidt et al, 2019Scheidt et al, , 2020Scheidt et al, , 2021Schneider et al, 2021;Linse et al, 2020;Emmenegger et al, 2021;Aprile et al, 2020;Ausserwöger et al, 2022). MDS has previously been applied to measure affinities of interactions of molecular chaperones (Scheidt et al, 2019(Scheidt et al, , 2021Schneider et al, 2021), of therapeutic antibodies (Arosio et al, 2016;Linse et al, 2020;Aprile et al, 2020) and design peptides (Sahtoe et al, 2023) with amyloid structures, as well as the characterisation of protein-DNA interactions (Ausserwöger et al, 2022), protein-membrane interactions (Zhang et al, 2020;Baumann et al, 2023), and of protein mixtures (Scheidt et al, 2020). Nevertheless, only enzyme-linked immunosorbent assays (ELISA) (Engvall, 1980;Engvall et al, 1971;Engvall and Perlmann, 1972;Ueda et al, 1996) and bead-based multiplex assays (Carson and Vignali, 1999;Fulton et al, 1997;Joos et al, Abbreviations...…”
Section: Introductionmentioning
confidence: 99%
“…Several different techniques have been successfully applied for the characterisation of molecular interactions in research, such as dynamic light scattering (DLS) (Malm and Corbett, 2019), isothermal titration calorimetry (ITC) (Pierce et al, 1999), microscale thermophoresis (MST) (Asmari et al, 2018), nuclear magnetic resonance (NMR) (Wilkins et al, 1999), surface plasmon resonance (SPR) (Mullett et al, 2000;Visentin et al, 2016Visentin et al, , 2018, and the here presented microfluidic diffusional sizing (MDS) (Arosio et al, 2016;Scheidt et al, 2019Scheidt et al, , 2020Scheidt et al, , 2021Schneider et al, 2021;Linse et al, 2020;Emmenegger et al, 2021;Aprile et al, 2020;Ausserwöger et al, 2022). MDS has previously been applied to measure affinities of interactions of molecular chaperones (Scheidt et al, 2019(Scheidt et al, , 2021Schneider et al, 2021), of therapeutic antibodies (Arosio et al, 2016;Linse et al, 2020;Aprile et al, 2020) and design peptides (Sahtoe et al, 2023) with amyloid structures, as well as the characterisation of protein-DNA interactions (Ausserwöger et al, 2022), protein-membrane interactions (Zhang et al, 2020;Baumann et al, 2023), and of protein mixtures (Scheidt et al, 2020). Nevertheless, only enzyme-linked immunosorbent assays (ELISA) (Engvall, 1980;Engvall et al, 1971;Engvall and Perlmann, 1972;Ueda et al, 1996) and bead-based multiplex assays (Carson and Vignali, 1999;Fulton et al, 1997;Joos et al, Abbreviations...…”
Section: Introductionmentioning
confidence: 99%
“…Aβ42 undergoes liquid-liquid phase separation in vitro. An intensive effort has been focused on exploring how different co-factors, such as lipids, which make up to 60% of the dry brain mass (17), affect the rates of distinct Aβ42 fibrillation steps (18)(19)(20)(21)(22)(23). Changes in brain lipidome have been linked to the development of AD, giving rise to a great interest in understanding the role of lipid surfaces in Aβ42 aggregation in AD (24).…”
Section: Resultsmentioning
confidence: 99%
“…Several arguments are in favor of the intracellular membrane production and aggregation of Aβ. Also, a very recent in vitro study elegantly demonstrated that in various biomimetic model organelle membranes, Aβ 1–42 aggregation kinetics is influenced by lipid composition, especially in the inner endosomal leaflet comparable to the outer leaflet of the plasma membrane . In addition, numerous studies have described the very high affinity of oligomeric Aβ peptides for membranes and membrane lipids but without describing consensually the types of interactions .…”
Section: Introductionmentioning
confidence: 99%
“…Also, a very recent in vitro study elegantly demonstrated that in various biomimetic model organelle membranes, Aβ 1−42 aggregation kinetics is influenced by lipid composition, especially in the inner endosomal leaflet comparable to the outer leaflet of the plasma membrane. 17 In addition, numerous studies have described the very high affinity of oligomeric Aβ peptides for membranes and membrane lipids but without describing consensually the types of interactions. 18 In differentiated PC12 cells and N2a cells stably expressing APPswe and PS1, the Aβ 1−42 peptide was also found tightly associated with the lysosomal membrane, while its proportion in the lysosomal lumen is minimal.…”
Section: ■ Introductionmentioning
confidence: 99%